Salvage robot-assisted radical prostatectomy (sRARP) for radiation resistant prostate cancer in a group of initially high risk patients - Lamichhane, Nirmal; Dowrick, Adam S.; Axcrona, Ulrika; Brennhovd, Bjørn; Fosså, Sophie D.; Axcrona, Karol (Nepalese Journal of Cancer, 2017)
Introduction: Salvage robot-assisted radical prostatectomy (sRARP) is seen as an attractive option for salvage treatment of radiation therapy -recurrent prostate cancer (PC), thanks in part to the good visualisation that is possible using this modality. However, the results of fewer than 200 salvage sRARPs have been published in the literature. We report the outcomes in a cohort of initially high risk patients of robot-assisted radical prostatectomy as salvage local therapy for radiation-resistant PC in a Scandinavian healthcare setting. Materials and methods: A retrospective review of the charts of all patients who underwent sRARP for biochemical failure (BCF) after primary radiation treatment for localised PC at a single institution was performed. Results: Twenty-two patients, median age 67 years (range 57 to 72), had sRARP performed between June 2008 to July 2013. A median follow-up of 26 months (range 2 to 63) was observed. Perioperative complications occurred in 4 patients (18%), with one patient sustaining a rectal injury. Histo-pathological diagnosis was pT2 in three, pT3a in five, pT3b in twelve and pTx in one patient. Ten patients (45%) had a positive surgical margin (PSM). At follow-up, 54 % of patients were free of biochemical progression and 41% were continent. Conclusions: We showed that salvage RARP is technically feasible in a cohourt of patients with predominantly high risk disease. This study adds to the limited data already in the literature, demonstrating the high frequency of locally advanced (pT3b) PC, a patient group that is usually not included in salvage treatments, as e.g. high frequency ultrasound or salvage brachytherapy. Further, given that the historical barriers to salvage RP with higher rates of rectal injury and poor urinary control no longer seem to be applicable in the modern era, we think that more patients should be considered candidates for this potentially curative salvage treatment of radiation-resistant PC. However, long-term follow-up is needed to confirm if the additional burden on these patients confers to oncological control following the procedure.